Epidemiology of Late Health Effects in Ukrainian Chornobyl Cleanup Workers. Issue 1 (July 2018) - Bazyka, Dimitry; Prysyazhnyuk, Anatoly; Gudzenko, Natalya; Dyagil, Iryna; Belyi, David; Chumak, Vadim; Buzunov, Volodymyr
Abstract : Abstract: This article summarizes the results of 30 y of follow-up of cancer and noncancer effects in Ukrainian cleanup workers after the Chornobyl accident. The number of power plant employees and first responders with acute radiation syndrome under follow-up by the National Research Center for Radiation Medicine decreased from 179 in 1986–1991 to 105 in 2011–2015. Cancers and leukemia (19) and cardiovascular diseases (21) were the main causes of deaths among acute radiation syndrome survivors (54) during the postaccident period. Increased radiation risks of leukemia in the Ukrainian cohort of 110, 645 cleanup workers exposed to low doses are comparable to those among survivors of the atomic bomb explosions in Japan in 1945. Additionally, an excess of chronic lymphocytic leukemia was demonstrated in the cleanup workers cohort for 26 y after the exposure. A significant excess of multiple myeloma incidence [standardized incidence rate (SIR) 1.61 %, 95% confidence interval (CI) 1.01–2.21], thyroid cancer (SIR 4.18, 95% CI 3.76–4.59), female breast cancer (SIR 1.57 CI 1.40–1.73), and all cancers combined (SIR 1.07; 95% CI 1.05–1.09) was registered. High prevalence was demonstrated for cardio- and cerebrovascular diseases and mental health changes. However, the reasons for the increases require further investigation. To monitor other possible late effects of radiation exposure in Chornobyl cleanup workers, analytical cohort and case-control studies need to include cardiovascular pathology, specifically types of potentially radiogenic cancers using a molecular epidemiology approach. Possible effects for further study include increased rates of thyroid, breast, and lung cancers and multiple myeloma; reduction of radiation risks of leukemia to population levels; and increased morbidity and mortality of cleanup workers from cardio- and cerebrovascular pathology.